2021
DOI: 10.1183/16000617.0260-2020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of latent tuberculosis infection on health and wellbeing: a systematic review and meta-analysis

Abstract: The impact of latent tuberculosis infection (LTBI) on health and wellbeing is not well understood. This review aims to evaluate the health and wellbeing of individuals with LTBI. A systematic literature search was performed to assess studies reporting patient-reported outcomes in LTBI management including health-related quality of life (HRQoL), health utilities, disease burden and experience of individuals with LTBI. A pooled analysis was performed to estimate the effect of LTBI on HRQoL.A total of 4464 studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Treatment for severely drug-resistant TB can take up to two years and includes a cocktail of progressively unpleasant medicines with side effects ranging from nausea to irreversible hearing loss. When it comes to health-related quality of life (HRQoL) in persons with TB, it was discovered that it is much poorer than in those without TB [26].…”
Section: Public Health Impactmentioning
confidence: 99%
“…Treatment for severely drug-resistant TB can take up to two years and includes a cocktail of progressively unpleasant medicines with side effects ranging from nausea to irreversible hearing loss. When it comes to health-related quality of life (HRQoL) in persons with TB, it was discovered that it is much poorer than in those without TB [26].…”
Section: Public Health Impactmentioning
confidence: 99%
“…(MVD2019.7.0.0) program was used for the validation of molecular docking. The docking scoring function MolDock score energy, E score is defined by (1), where E inter is the ligand-receptor interaction energy and E intra is the internal energy of the ligand. According to (2) equation, E inter is calculated.…”
Section: Molecular Docking Proceduresmentioning
confidence: 99%
“…Tuberculosis (TB) is one of the top ten causes of global mortality, with an estimated 1.5 million deaths due to TB in 2018, globally [1]. Mycobacterium TB (MTB) infection in humans does not usually lead to active disease.…”
Section: Introductionmentioning
confidence: 99%
“…The volunteers in this study were enrolled and subjected to the analysis using the IFN-γ release assay (QuantiFERON-TB Gold In-Tube (QFT), Qiagen, CA, USA) along with clinical, microbiological, and radiographical examinations. The criteria for enrollment were as follows: (1) patients with active TB (ATB group in this study) showed clinical and radiographical features of tuberculosis and were confirmed by sputum smear or culture. Moreover, they did not receive anti-TB treatment before sample selection.…”
Section: Subjects In This Study and Sample Collectionmentioning
confidence: 99%